The Impact of Financial Distress, Women on Boards and Profitability on Corporate Tax Avoidance - Tri Laksono, Avit; Handayani, Erna (PT FORMOSA CENDEKIA GLOBAL, 2024)
Taxes are one of the highest sources of state income, especially in developing countries, but taxes are actually one of the biggest expenses for companies which will reduce the profits they get. Companies will of course be encouraged to reduce expenditure to increase income, one of which is by avoiding taxes. Tax avoidance is a strategy employed to lawfully minimise company expenditures by reducing the amount of corporate tax paid to the government. While this practise is permissible, it has the potential to diminish the state's tax revenue. The aim of this study was to examine the impact of financial distress, women on boards, and profitability on corporate tax avoidance. The population for this study consisted of companies that were classified under the LQ45 category on the Indonesia Stock Exchange (BEI) between 2013 and 2022. The sample was selected using a purposive sampling technique. This study use the statistical method of multiple regression for data analysis. The results of these study indicated that research with financial distress, Profitability, and Women on Board Commissioners has positively effect on corporate tax avoidance. Meanwhile, the Women on Board Director had no effect on tax avoidance.